Riskanalysverktyg för stålindustrin : Ett verktyg för riskanalys, anpassat för oönskade och riskfyllda arbetsmoment som innebär fysisk handpåläggning vid produktionsstörning på Ovakos anläggning i Hällefors - Ylvén, Moa (2016)
This master thesis concerns work environmental risks that are a part of the modern steel industry. The result is a tool that can be used for identifying unwanted risks, which usually are hard to identify. The content of the tool is based on results from extensive literature studies, statistical analyses and qualitative in-depth interviews with the persons that are exposed for the risks on a daily basis.The master thesis project was conducted during the spring of 2015 as a final project of the civil engineering program Technical design at Luleå University of Technology. Ovako AB was the outsourcer and the studies were carried out on their production plant in Hällefors. The production in Hällefors included the making of hot rolled, peeled and ground bar and wire and also the manufacturing of pre-components from bars. The plant in Hällefors was certified with ISO 14001, OHSAS 18001, ISO 9001 and TS 16949.The statistical analyses showed that crushing injuries and other soft tissue injuries were the most common type of injuries at the production plant in Hällefors during the time period 1/1 2014 – 28/4 2015. The second most common type of injuries was cutting injuries, sprains and muscle strains. During the same time period the most frequently reported reasons for an injury or a close call were getting hit by a flying or a falling object. The second most common reason was getting stuck or crushed between objects. The qualitative in-depth interviews pointed out that crushing injuries, cutting injuries, injuries from falls, burns and repetitive strain injuries were the most common injury types at the production plant in Hällefors. The interviewees described that tangled bundles, crooked bars, short bars, sharp edges on cut bars, work up on machines and loading tables, slippery surfaces, welding spatters and the manoeuvring of overhead cranes and vehicles are the biggest reasons why accidents occurs.The tool has the form of a checklist and the content is, based on the results from the study, divided in five different ...